Respon Siswa Madrasah Aliyah Terhadap Pelatihan Pembuatan Kefir - Nani Kurnia; Andi Mu'nisa; Kusdianawati; Muhammad Junda (Jurusan Matematika FMIPA UNM, 2024)
Kefir is an average result of fermented milk using kefir grains as a starter that contains lactic acid bacteria and yeast. Kefir drinks are believed to affect the balance of intestinal microbes positively. In developing countries, kefir is produced on a factory scale and is marketed internationally by various brands. This differs in Indonesia; kefir is still produced on a small scale and sold in limited quantities and in restricted areas. Considering the benefits and market potential, the public must know about the benefits and how to make kefir. Therefore, knowledge transfer activities and training in making kefir to the community are very important to be carried out, one of which is to school students. The school students who can be selected are high. Therefore, this activity aims to provide training for MA DDI Mattoangin, Bantaeng Regency students training in making kefir. The implementation method used in this activity consists of 4 stages: presentation, demonstration, practice, and evaluation. This activity has been carried out at MI DDI Mattoangin, Bantaeng Regency, and was attended by 11 participants. The participants enthusiastically followed all the activities, which ended with following and paying attention to the presentation, the kefir-making demonstration, practicing kefir-making, and filling out the questionnaire